Climate change adaptation and disaster risk reduction issues and challenges - Kyoto University, Japan; University of the Philippines Los Baños, The Philippines; Universiti Kebangsaan Malaysia, Bangi, Malaysia; Shaw, Rajib; Pulhin, Juan M.; Pereira, Joy Jacqueline (Community, environment and disaster risk management, 2010)
Climate Change Adaptation (CCA) and Disaster Risk Reduction (DRR) are closely associated. After the Bali Conference of Parties (COP) 2007, there has been significant awareness in global and national level to make collective focus on CCA and DRR. There exists some literature on CCA, however, the linkages with the DRR is not clear. The Nairobi Work Program (NWP), facilitated by the UNFCCC (UN Framework of Convention on Climate change) and the Parties have found specific scope of actions to enhance the CCA and DRR agenda in developing countries. Different national and international agencies have started undertaking initiatives on this aspect but very few concrete measures have been implemented. In this context, this volume identifies a few specific entry points of CCA and DRR exemplifying sector based approach. The book will help the researchers and practitioners to have a better idea on the current trend of research in the field, and will provide basic knowledge on this important topic. The book has also provided a few key policy related issues in this topic.